1998
DOI: 10.1115/1.2841786
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Squealer Tip on Rotor Heat Transfer and Efficiency

Abstract: Calculations were performed to simulate the tip flow and heat transfer on the GE-E3 first-stage turbine, which represents a modern gas turbine blade geometry. Cases considered were a smooth tip, 2 percent recess, and 3 percent recess. In addition, a two-dimensional cavity problem was calculated. Good agreement with experimental results was obtained for the cavity calculations, demonstrating that the k–ω turbulence model used is capable of representing flows of the present type. In the rotor calculations, two d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(60 citation statements)
references
References 14 publications
1
59
0
Order By: Relevance
“…Numerical methods have been widely used to study the thermal performance of film cooling in high-pressure turbines, e.g., Ameri [21] and Yang et al [22]. Computational fluid dynamics (CFD) tools were found to be able to produce good predictions of the thermal performance of the tip leakage flow in a number of studies, both at subsonic conditions (e.g., Zhou et al [9]) and at transonic conditions (e.g., Zhang et al [18]).…”
Section: Numerical Methods and Validationmentioning
confidence: 99%
“…Numerical methods have been widely used to study the thermal performance of film cooling in high-pressure turbines, e.g., Ameri [21] and Yang et al [22]. Computational fluid dynamics (CFD) tools were found to be able to produce good predictions of the thermal performance of the tip leakage flow in a number of studies, both at subsonic conditions (e.g., Zhou et al [9]) and at transonic conditions (e.g., Zhang et al [18]).…”
Section: Numerical Methods and Validationmentioning
confidence: 99%
“…CFD tools are known to be able to produce good predictions of the aerothermal performance of the tip-leakage flow: e.g., Schabowski and Hodson [2] and Ameri et al [5]. Furthermore, CFD results can provide insight into the physics of the tip-leakage flow.…”
Section: Methodsmentioning
confidence: 99%
“…There are some studies showed that the cavity tip provides very small aerodynamic benefits or even no benefit over a flat tip. For example, based on numerical simulations of a rotor at a rotational speed of 8450 rpm, Ameri et al [5] found a reduction in the tip-leakage mass flow by using a cavity tip instead of a flat tip, but no change in the efficiency was obtained.…”
mentioning
confidence: 99%
“…Ameri et al [18] numerically studied the flow and heat transfer on the squealer tip which had a 2% and 3% cavity recess. Ameri et al [19,20] numerically investigated the effect of tip clearance and casing (shroud) recess on heat transfer and stage efficiency for different recess depths.…”
Section: Introductionmentioning
confidence: 99%